1993
DOI: 10.1159/000126414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma-Aminobutyric Acid-A Receptor Antagonist Bicuculline, on the Electrical Activity of Luteinizing Hormone-Releasing Hormone Pulse Generator in the Ovariectomized Rat

Abstract: The role of GABA neurons in the control of pulsatile release of LHRH was investigated by checking the effect of the GABAa receptor agonist, muscimol, and antagonist, bicuculline, on the electrical activity of the luteinizing hormone-releasing hormone (LHRH) pulse generator in the ovariectomized rat fitted with chronically implanted electrode arrays in the medial basal hypothalamus. In untreated control animals, the hypothalamic multiunit activity (MUA) exhibited, at an average of 20.5-min intervals, characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
4
10
1
Order By: Relevance
“…Infusion of 20 µ M GABA prolonged the interval and decreased the amplitude of GnRH pulses, resulting in a decrease in mean GnRH release. These GABA effects on pulsatile GnRH release are in good accordance with previous reports; a GABA or GABA A receptor system exerted an inhibitory influence on LH release in gonadectomized rats [35, 36, 37, 38, 39, 40, 41]and on GnRH release in rat hypothalamic fragments [42, 43, 44, 45], although some groups have reported a stimulatory influence instead [46, 47, 48, 49, 50, 51]. Together with morphological observations, the present results provide evidence that the inhibition of pulsatile LH release by GABA is caused by the direct action of GABA on GnRH neurons.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Infusion of 20 µ M GABA prolonged the interval and decreased the amplitude of GnRH pulses, resulting in a decrease in mean GnRH release. These GABA effects on pulsatile GnRH release are in good accordance with previous reports; a GABA or GABA A receptor system exerted an inhibitory influence on LH release in gonadectomized rats [35, 36, 37, 38, 39, 40, 41]and on GnRH release in rat hypothalamic fragments [42, 43, 44, 45], although some groups have reported a stimulatory influence instead [46, 47, 48, 49, 50, 51]. Together with morphological observations, the present results provide evidence that the inhibition of pulsatile LH release by GABA is caused by the direct action of GABA on GnRH neurons.…”
Section: Discussionsupporting
confidence: 92%
“…As noted above, it has been suggested that GABA inhibits GnRH release through the GABA A receptor system [42, 43, 44, 45]. But bicuculline did not affect the electrical activity of the GnRH pulse generator or the pulsatile LH release [40]. Therefore, we concluded that, although the GnRH pulse generator has a GABA A receptor system, this does not play a role in the generation of GnRH pulses.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We also tried to measure the response of the pulse generator to the opiate receptor antagonist naloxone, which is very effective in altering the activity in young rats [2, 20, 21, 22, 23]. …”
Section: Introductionmentioning
confidence: 99%